Challenging the gifted child [ an open approach to working with advanced young readers - Stevens, Margaret (Jessica Kingsley Publishers, 2009)
Gifted children are quick on the uptake, can be frustrated by repetition and easily become impatient when unchallenged. This work explains the criteria for choosing appropriate reading for the child